The dose-response relationship between sex hormones and hyperuricemia in different gender: NHANES 2013-2016 - Li, Guo-yun; Qian, Xu-dong; Ma, Chun-ming; Yin, Fu-zai (Frontiers in Endocrinology, 2022)
Objectives: To access the dose-response relationship between sex hormones and hyperuricemia (HUA), and to find the cut-off value in different gender. Methods: 9,685 participants were derived from the database of National Health and Nutrition Examination Survey (NHANES). Restricted cubic spline (RCS) analysis were applied to explore the relationship between sex hormones and HUA after adjusting for confounding factors by propensity score match (PSM). Logistic regression was used to estimate the odds ratio (OR) and 95% CI. Results: The prevalence of HUA was 15.13% in female participants and 22.30% in male participants. Logistic regression analysis showed that estradiol (E2) was independently associated with HUA for a P value of 0.003 and 0.011 in both female and male participants, respectively. Testosterone (T) was only independently associated with HUA in male participants (P<0.001) but not in female participants (P = 0.5981). RCS analysis showed a dose-response relationship between sex hormones and HUA. The risk of HUA increased as E2 lower than 29.6pg/ mL in female participants and T lower than 389.1ng/ dL in male participants. E2 higher than 23.6pg/ml was an independent risk factor for HUA in male participants. Conclusion: A dose-response relationship was found between sex hormones and HUA. The cut-off value of E2 in male and female participants was 29.6pg/ mL and 23.6pg/ mL, respectively, and the cut-off value of T in male participants was 389.1ng/ dL. These results provide a reference for preventing HUA and hormone supplement therapy.